The humanities as conceptual practices: The formation and development of high‐impact concepts in philosophy and beyond. (29th March 2022) - Haueis, Philipp; Slaby, Jan
Abstract : This paper proposes an analysis of the discursive dynamics of high‐impact concepts in the humanities. These are concepts whose formation and development have a lasting and wide‐ranging effect on research and our understanding of discursive reality in general. The notion of a conceptual practice, based on a normative conception of practice, is introduced, and practices are identified, on this perspective, according to the way their respective performances are held mutually accountable. This normative conception of practices is then combined with recent work from philosophy of science that characterizes concepts in terms of conceptual capacities that are productive, open‐ended, and applicable beyond the original context they were developed in. It is shown that the formation of concepts can be identified by changes in how practitioners hold exercise of their conceptual capacities accountable when producing knowledge about a phenomenon. In a manner similar to the use of operational definitions in scientific practices, such concepts can also be used to intervene in various discourses within or outside the conceptual practice. Using the formation of the concepts "mechanism" and "performative" as examples, the paper shows how high‐impact concepts reconfigure what is at issue and at stake in conceptual practices. As philosophy and other humanities disciplines are its domain of interest, it is a contribution to the methodology of the humanities.